INFORMATIONAL SYSTEM FOR PROGRAM PERFORMANCE ESTIMATION - A.V. POBEDYONNY (Advanced Engineering Research)
Huge amount of similar informational systems available today inevitably causes the problem of 'the right choice'. There are plenty of ways to estimate product quality today, however most of them either gives subjective results or requires plenty of computations to be made by user. An alternate way of comparing two or more infromational systems by user-defined quality factors is described in the following article.